Dietary supplementation with a high dose of daidzein enhances the antioxidant capacity in swine muscle but experts pro-oxidant function in liver and fat tissues. Issue 1 (December 2016) - Chen, Wei; Ma, Xianyong; Lin, Yingcai; Xiong, Yunxia; Zheng, Chuntian; Hu, Youjun; Yu, Deqian; Jiang, Zongyong
Abstract Background Although isoflavones are natural dietary antioxidants, they may have toxicological effects. This study aimed to evaluate the redox system in tissues of finishing pigs by supplementation with high dose of daidzein (640 mg/kg). Results The supplementation of high dose of daidzein for 64 d increased the activity of superoxide dismutase and total antioxidant capacity in longissimus muscle but down-regulated the expression of reactive oxygen species (ROS)-producing enzyme NADPH oxidase-2 and cyclooxygenase-2. In contrast, high-level supplementation with daidzein exerted pro-oxidant changes in back fat, abdominal fat, liver, and plasma, as reflected by increased contents of malondialdehyde, a lipid peroxidation product, in these tissues. Furthermore, daidzein supplementation resulted in higher expression of ROS-producing enzymes, including NADPH oxidase-1 and cyclooxygenase-1 in liver, 5-lipoxygenase (5-LOX) in backfat and NADPH oxidase-2 both in abdominal fat and backfat. The supplementation of daidzein did not affect meat quality parameters in longissimus muscle, including marbling score, eye muscle areas, intramuscular fat, shear force, drip loss, pH and meat color. Conclusions This experiment suggests that dietary supplementation of finishing pigs with daidzein at a high dose level improves redox status in muscle but exerts pro-oxidant effect in liver and fat tissues.